Punica granatum Peel Waste - An Underutilized Substrate of Therapeutic Potential: An Overview - Noor, Uroosa; Soni, Shashi; Gupta, Ena (Recent Advances in Food Nutrition & Agriculture, 2022)
India is the second largest consumer and producer of fruits globally. It leads to ample solid waste per year from fruit processing industries that have been proven hazardous to the surroundings. Punica granatum (Pomegranate) belongs to the Lythraceae subfamily Punicoideae, which exhibits immense nutritional properties and delicious flavoring components. The weight of this fruit mainly consists of peel, i.e., 50%, followed by 40% of arils and 10% of seeds. Thus, the major byproduct is peel that holds many valuable bioactive compounds in higher concentrations viz saponins, carotenoids, steroids, polyphenols, quercetin derivatives, caffeic acid, phenolic acids, flavonoids, ellagitannins, p-coumaric acid, chlorogenic acid, quinic acid, anthocyanidins, triterpenoids, glycosides, tannins, and many more. Consequently, it results in wideranging therapeutic applications, including antioxidative, anti-microbial, antihypertensive, anticarcinogenic, anti-genotoxic, anti-inflammatory, glucoregulation, cardio-protective, hepatoprotective and nephroprotective effects along with prebiotic potential. Considering their nutritional and therapeutic aspects, these peels can be used for many purposes rather than being disposed off. With a value-added approach, it is utilized in many food and non-food sectors. So, this review aims to explore the therapeutic potential of P. granatum peel and enlighten its diverse applications in the food industry.
Keywords: solid waste